Ranking of Russian higher education institutions; Higher Education in Europe; Vol. 32, Iss. 1, April - Pokholkov Y. P. Yuri Petrovich; Чучалин А. И. Александр Иванович; Agranovich B. L. Boris Lvovich; Mogilnitsky S. B. (2007, 2007)
This article considers some patterns of ranking higher education institutions which are used in the Russian Federation to reveal strengths and weaknesses in meeting the national individual, societal and state-related needs, as well as those of the international academic community concerning relevant information on Russian higher education institutions